CUSTOMER OBSESSED COMPANY why customer success is becoming the only competitive advantage cloth. - NOT AVAILABLE (JOHN WILEY, 2019)
If leaders aren't integrating their digital offerings into a philosophy of Customer Success, they will be defeated in the next decade, because technical excellence and other traditional competitive advantages are becoming too easy to imitate. The Customer Success Economy offers examples and specifics of how companies can transform. It addresses the pains of transforming organizational charts, leadership roles, responsibilities, and strategies so the whole company works together in total service to the customer. -Shows leaders how their digital implementations will make them more Amazon-like -Helps you deliver recurring revenue -Shows you how to embrace customer retention -Demonstrates the importance of "churning" less Get that competitive advantage in the most relevant and important arena today'making and cultivating happy customers.